Doxycycline versus Curcumin for Inhibition of Matrix Metalloproteinase Expression and Activity Following Chemically Induced Inflammation in Corneal Cells - Zareh, Hamed; Shahriary, Alireza; Razei, Ali; Ameri, Rouhollah; Fasihi-Ramandi, Mehdi; Aghamollaei, Hossein (Journal of Ophthalmic and Vision Research, 2024)
Purpose: Sulfur mustard (SM) is a potent blistering agent. This alkylating chemical agent has extremely toxic effects on the eye. MMP-2 and MMP-9 are the two most important matrix metalloproteinase enzymes involved in the pathology of chemical eye injuries. Curcumin is regarded as a natural anti-inflammatory agent. This study aims to compare the anti-inflammatory effects of curcumin versus doxycycline on chemically induced corneal injuries. Methods: The HCE-2 cell line was used as a model for corneal cells. The effective concentrations of 2-chloroethyl ethyl sulfide (CEES) – as an analog of SM – doxycycline, and curcumin were determined using the MTT assay. The gene expression of MMP-2, MMP-9, and tissue inhibitors of metalloproteinase (TIMP-1) was evaluated by the real-time PCR method. Also, the activity of MMP-2 and MMP-9 enzymes was determined by zymography. Results: The expression of the MMP-2 and MMP-9 genes increased 5- and 3.3-fold after exposure to CEES, respectively. Following the treatment with curcumin and doxycycline, MMP- 2 expression decreased significantly. Also, after treatment with curcumin and doxycycline, the MMP-9 expression decreased 2.5- and 1.6-fold, respectively. The reduction in activity was 32% for MMP-2 and 56% for MMP-9 after treatment with curcumin. The corresponding values were 12% and 40% following doxycycline treatment. There was no significant difference between the effects of curcumin and doxycycline on reducing MMP-2 expression, but the difference was statistically significant in the case of MMP-9. Conclusion: Doxycycline and curcumin can inhibit MMP expression and activity in chemically exposed corneal cells. Curcumin has a greater ability than doxycycline to inhibit MMP-2 and MMP- 9 enzymes; however, the difference is statistically significant only in the case of MMP-9. After further validation, these substances can be introduced as anti- inflammatory agents to treat corneal chemical burns.